Aplikasi Latihan Kombinasi Zig–Zagteknik Dan Pengaruhnya Terhadap Kecepatan Tendangan Sabit Pesilat Putra Jpok Fkip Universitas Sebelas Maret Surakarta - MUHAD FATONI; Nurhidayat Nurhidayat; Eko Sudarmanto (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
he purpose of this study was to determine: (1) The effect of Zig-zag-Technique Combination Exercise application on the speed of the JPOK Son's Sabit Kick Fighting FKIP Sebelas Maret University Surakarta. This research is using experimental method. The subject of this research is the son of the fostering of the achievement of pencak silat JPOK in Sebelas Maret University Surakarta in 2012 totaling 20 people. The data collection technique used in this study was a 10-second sickle kick speed test. Data analysis techniques used with t test with a significance level of 5%. The results of the research are as follows: (1) There is a significant effect after the application of Zig-Zag Combination Technique on the Speed ​​of JPOK Putra's Fighter's Sabit Kick FKIP Sebelas Maret University Surakarta in 2012. From the calculation, the t-count is 2,242 and t-table with a significance level of 5% and n = 10 of 2,228. Improved index contributions that are able to be given a technical zigzag combination exercise are 14.40%. The research conclusions are as follows: (1) There is a significant effect of the technical zigzag combination training application on the speed of sickle kick on the son of the Pencak Silat JPOK Achievement in 2012 Sebelas Maret University Surakarta